(untitled) (Journal of Science and Technology, 2016)
Moringa oleifera Lam. is a multipurpose tropical dry habitat tree used throughout history for its ‘medicinal\’, nutritious, water purification and several other properties. Propagating Moringa spp. by seeds is now becoming difficult due to the over-utilization of the plant, most importantly the seeds, which are currently in greater demand chiefly for oil production used for lubricating and powering machines, and in the cosmetic industry. The other means of breeding is by normal vegetative propagation that employs stem hardwood as long as 2m. This is threatening its production as well since greater amount of propagules is often wasted. Stem maturity, that is, age of cuttings (i.e. hardwood, semi-hardwood and softwood) and stem-cutting length were thus studied to examine their significance on sprouting using a 3 x 4 factorial experiment in Randomized Complete Block Design (RCBD) in two blocks. Split, split-plot analysis was conducted using time as a sub-subplot. Factors examined were the number of sprouted stem-cuttings and shoots as well as shoot length for a period of ten weeks with cuttings planted in natural soil in polythene bags. Hardwood cuttings sprouted best having the highest mean value for the number of shoots produced followed by semi-hardwood cuttings all of length 30cm. Based on the present investigation, it has been found that instead of employing the conventional seeds, which are in short supply and longer stem cuttings for the propagation of Moringa spp. worldwide, hardwoods or semi-hardwoods as short as 30cm can now be employed to ensure their sustainability.